2001
DOI: 10.1006/jtbi.2000.2198
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Bacteriophage Therapy as a Density-dependent Kinetic Process

Abstract: Studies of bacteriophage as therapeutic agents have had mixed and unpredictable outcomes. We argue that interpretation of these apparently paradoxical results requires appreciation of various density-dependent threshold e!ects. We use a mathematical model to delineate di!erent categories of outcome, including therapy by simple inundation, by active biocontrol, and by delayed active biocontrol. Counter-intuitively, there are situations in which earlier inoculation can be less e$cacious, and simultaneous inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
229
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(244 citation statements)
references
References 15 publications
6
229
1
3
Order By: Relevance
“…Their model focused on the maintenance of phage populations, which thus do not admit nonreplicating phages. Payne & Jansen (2001) generated the result in our model 1 as a contrast to the effect produced by a replicating phage and thus did not explore it. Wodarz developed a model of viral treatment of tumour cells (Wodarz 2001(Wodarz , 2003; one version of that model considered a non-replicating virus (Wodarz 2003), but that model did not address how much virus was needed, and there was no viral loss when infecting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their model focused on the maintenance of phage populations, which thus do not admit nonreplicating phages. Payne & Jansen (2001) generated the result in our model 1 as a contrast to the effect produced by a replicating phage and thus did not explore it. Wodarz developed a model of viral treatment of tumour cells (Wodarz 2001(Wodarz , 2003; one version of that model considered a non-replicating virus (Wodarz 2003), but that model did not address how much virus was needed, and there was no viral loss when infecting cells.…”
Section: Discussionmentioning
confidence: 99%
“…The practical applicability of this approach may be compromised by the minimum density of host cells that are suggested to be required for phage replication (Payne et al, 2000;Payne & Jansen, 2001). Nevertheless it was demonstrated that phages can be effective biocontrol agents when the population of host cells is as low as 46 CFU/cm 2 (Greer, 1988).…”
Section: Phage Biocontrol In Food Materialsmentioning
confidence: 99%
“…Ignoring bacterial growth (a m = 0) and viral replication (L = 0), the simulation shows viral attachment to bacteria (total bound virus) during the first few hours after introduction of phage at 100-to-one phage-host ratio. Such phage to host ratios are appropriate for so-called "passive phage therapy" which relies on first generation phage to overwhelm bacteria [22,23]. Note that increasing levels of bound virus mean decreasing numbers of free virus which mean fewer new infections.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…However, as multidrug resistant bacteria have become an enormous public health problem, there is a renewed interest in phage therapy [17,20,22,23,4,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation